ON THE OCCURRENCE OF MACROBRACHIUM LAMARREI (H. MILNE EDWARDS) IN THE RAMGARH LAKE, GORAKHPUR, WITH A NOTE ON THE VARIATIONS OF ITS ROSTRAL CHARACTERS - Omkar, Ram Murty; Shukla, G S (Indian Journal of Fisheries, 2011)
The occurrence of Macrobrachiitm lamarrei (H. Milne Edwards) in the Ramgarh lake, Gorakhpur, is reported. A detailed study of this M. lamarrei showed some differences in the rostral characters when compared to the previously known subspecies M. lamarrei lamarrei and M. lamarrei lamarroides (Tiwari 1952). These difference are discussed